#### Answer

$\sqrt[10] {y^{9}}$

#### Work Step by Step

$\sqrt[6] y\sqrt[3] y\sqrt[5] {y^{2}}=y^{1/6}y^{1/3}y^{2/5}=y^{1/6+1/3+2/5}=y^{9/10}=\sqrt[10] {y^{9}}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\sqrt[10] {y^{9}}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.